Optimisation of Agricultural Crop Allocation in Sustainable Biofuel Production and Energy Security Strategies - Tokarchuk, Dina; Lohosha, Roman; Tokarchuk, Oleksii; Dmytryk , Oleg (Dr. Viktor Koval, 2026)
Background. Energy and food security, as well as resilience to climate change, are key priorities in development strategies. Increasing prices of conventional energy resources and their uneven distribution across countries are major drivers of the development of renewable energy sources. The production and use of biofuels play a crucial role among renewable energy sources, reducing dependence on imported conventional fuels and creating new employment opportunities. Purpose. This study aims to develop scenarios for the production and consumption of liquid biofuels in Ukraine to increase energy security and ensure sustainable development. Findings. The production of liquid biofuels revealed that leading countries producing bioethanol and biodiesel often have traditional energy sources but are diversifying their energy portfolios. An algorithm for choosing between the food and energy use of crops was proposed, based on key selection criteria such as the level of domestic crop provision, the level of national energy security, and the efficiency of using crops for energy purposes relative to exports. This study identified the potential for bioethanol and biodiesel production in Ukraine based on export scenarios. This demonstrates Ukraine's potential to meet its needs and export finished bioenergy products (biofuels) to European and global energy markets. Three comprehensive scenarios for the production and consumption of biofuels in Ukraine up to 2035 were developed with target indicators for the substitution of traditional fuels at levels of 6%, 12% and 20%, respectively. The required areas for sowing optimal crops (wheat (20%), corn (40%), sugar beet (40%) for bioethanol and rapeseed (100%) for biodiesel) were calculated. To achieve the target indicators, these areas will amount to 1.8%, 3.6%, and 5.9% of the average crop area in Ukraine in 2020-2023, which demonstrates that biofuel production will not threaten food security. Implications. Agricultural crop distribution for sustainable biofuel production and energy security strategies can serve as the basis for Ukraine’s long-term national bioenergy policy, thereby increasing energy security and achieving climate goals. Implementing integrated scenarios will require allocating the necessary cropping areas, but the analysis indicates this will not threaten food security.